Photocarrier radiometry for noncontact evaluation of space monocrystalline silicon solar cell under low-energy electron irradiation - 刘俊岩 宋鹏 王飞 王扬 (Chinese physics B, 2015)
A space monocrystalline silicon（c-Si） solar cell under low-energy（〈 1 MeV） electron irradiation was investigated using noncontact photocarrier radiometry（PCR）. Monte Carlo simulation（MCS） was employed to characterize the effect of different energy electron irradiation on the c-Si solar cell. The carrier transport parameters（carrier lifetime, diffusion coefficient, and surface recombination velocities） were obtained by best fitting the experimental results with a theoretical one-dimensional two-layer PCR model. The results showed that the increase of the irradiation electron energy caused a large reduction of the carrier lifetime and diffusion length. Furthermore, the rear surface recombination velocity of the Si：p base of the solar cell at the irradiation electron energy of 1 Me V was dramatically enhanced due to 1 MeV electron passing through the whole cell. Short-circuit current（I sc） degradation evaluated by PCR was in good agreement with that obtained by electrical measurement.